β-циклодекстринвмісний полімерний матеріал: синтез та властивості - Lyashenko, D. Yu. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2014)
As a result of the copolymerization reaction, an insoluble in water and organic solvents crosslinked β-cyclodextrin-containing polymer has been synthesized. The polymer is not destroyed due to prolonged contact with weakly acidic solutions, has a high sorption capacity with respect to benzoic acid and good sorption kinetic parameters. Sorption results obtained are analyzed in terms of a kinetic Lagergren model for the pseudo-first and the pseudo-second order processes as well as Langmuir and Freundlich models of equilibrium adsorption. It has been shown that the interaction of benzoic acid with β-cyclodextrin-containing polymer is described by Lagergren model for pseudo-second order processes (R = 0,999). The active sites of the material synthesized are β-cyclodextrin molecules and urethane groups forming hydrogen bonds between oxygen atoms of the carboxyl group of benzoic acid molecule and hydrogen atoms of the secondary amino groups of the binder.